In Digital Conditions, The Importance of Information Communication Technologies in Primary Classes (International Journal of Scientific Trends, 2023)
The article discusses the search for ways to develop education, increase its efficiency, and introduce new information technologies into education. It has been stated that the use of information and communication technologies in primary schools in a digital environment gives positive results, and it is necessary to properly organize the educational process in accordance with the hygienic standards established for primary classes.